2022
DOI: 10.17219/dmp/138636
|View full text |Cite
|
Sign up to set email alerts
|

Influence of dentofacial characteristics on the appearance of self-reported bullying: A review

Abstract: Bullying is a social problem that affects children and adolescents in particular. It deteriorates the selfesteem of its victims, decreases their quality of life and generates future psychological problems. The aim of this review was to determine the influence of dentofacial characteristics on the appearance of selfreported bullying through a literature review.A systematic search was carried out in the databases of international scientific literature on health sciences, including MEDLINE via PubMed, Scopus, LIL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…The low bond strength will result in lesser sealing ability and thereby explaining the result of this study. Bio-C is a novel bioceramic, non-resin which stimulates tissue regeneration 19 and the only ready-to-use cement with Tricalcium aluminates, providing the same biological interaction as MTA [ 53 , 54 ] although with improved manipulation and insertion, known to induce osteo-promotive and bone-remembering and thought to contribute to the mineralization process of the periapical tissue [ 55 58 ]. They are biocompatible have appropriates setting time, flow and radiopacity besides alkalinization capacity reaching pH of 10 in 21 days [ 56 , 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…The low bond strength will result in lesser sealing ability and thereby explaining the result of this study. Bio-C is a novel bioceramic, non-resin which stimulates tissue regeneration 19 and the only ready-to-use cement with Tricalcium aluminates, providing the same biological interaction as MTA [ 53 , 54 ] although with improved manipulation and insertion, known to induce osteo-promotive and bone-remembering and thought to contribute to the mineralization process of the periapical tissue [ 55 58 ]. They are biocompatible have appropriates setting time, flow and radiopacity besides alkalinization capacity reaching pH of 10 in 21 days [ 56 , 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…24 Bullying, which is common in society, is a social issue that particularly affects children and adolescents. 25,26 It has been expressed that children with certain malocclusions are more likely to be exposed to actions of teasing, name-calling, and physical bullying. 27 Duarte-Rodrigues et al 28 reported that children with a Class III malocclusion were more likely to experience bullying compared to those with a mild or absent malocclusion.…”
Section: Discussionmentioning
confidence: 99%